2014
DOI: 10.1371/journal.pone.0108226
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hypertension as a Risk Factor for Open-Angle Glaucoma: A Meta-Analysis of Population-Based Studies

Abstract: Background/AimsSystemic hypertension is thought to increase the risk for developing open-angle glaucoma (OAG) through several mechanisms. However, previous epidemiological studies have shown conflicting results regarding this potential association. We systematically evaluated this issue by conducting a meta-analysis of population-based studies.MethodsA comprehensive search for articles published before 31 March 2014 was performed using PubMed, Embase, and reference lists. The pooled odds ratio (OR) was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 39 publications
3
48
0
1
Order By: Relevance
“…Systemic hypertension showed a modest positive association with elevated intraocular pressure. 12 In our study, glaucoma was more in diabetic patients with HT. Connection between diabetes and simple glaucoma was observed in 1924 by Grafe.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Systemic hypertension showed a modest positive association with elevated intraocular pressure. 12 In our study, glaucoma was more in diabetic patients with HT. Connection between diabetes and simple glaucoma was observed in 1924 by Grafe.…”
Section: Resultssupporting
confidence: 48%
“…10,11 The incidence is more for high-tension glaucoma. 12 Recent studies have also demonstrated that the effects on the visual field due to elevation of intraocular pressure was related to diastolic ophthalmic artery pressure. Systemic hypertension showed a modest positive association with elevated intraocular pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the study postulate that low diastolic blood pressure can lead to decreased ocular perfusion pressures, which is consistent with the vascular hypothesis of glaucomatous optic neuropathy, whereas changes associated with chronic systemic hypertension, such as arteriosclerosis, can also decrease ocular perfusion [181]. A recent meta-analysis of 16 studies found that individuals with systemic hypertension had a pooled odds ratio of 1.2 for the development of glaucoma compared to normotensive individuals [182]. Several studies have, however, shown a positive correlation between IOP and systemic hypertension, particularly elevated systolic blood pressure [80,175,183189].…”
Section: Glaucoma Risk Factors and Correlation With Diabetesmentioning
confidence: 64%
“…Hypertension and diabetes mellitus are well-known risk factors for stroke 11. Although controversial, several large population-based studies have reported associations between hypertension and OAG12 or between diabetes mellitus and OAG 13. Chronic kidney disease is thought to be a risk factor for OAG, as well as for stroke,14 and there is a higher risk of glaucoma15 and higher intraocular pressure16 among patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%